Manajemen Sarana dan Prasarana Pendidikan dalam Menunjang Mutu Pembelajaran di MAN 2 Kota Semarang - Anna Amalia Silfi; Fahrurrozi Fahrurrozi (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2025)
Abstract: This article examines issues arising from the social fact that the availability of adequate educational facilities is not always accompanied by optimal management, particularly in terms of utilization, maintenance, and data-based management. In the context of modern education and demands for improved learning quality, facility and infrastructure management is a strategic factor because it directly affects the comfort, effectiveness, and quality of the teaching and learning process. This study uses a qualitative approach with a case study type. Data collection techniques were carried out through observation, in-depth interviews with the head of the madrasah, the deputy head of facilities and infrastructure, teachers, and students, as well as documentation. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing. The results of the study show that the management of facilities and infrastructure at MAN 2 Semarang City has been running quite well in terms of planning and procurement, and is supported by the availability of relatively complete facilities. However, it was found that the utilization of facilities was not yet evenly distributed, maintenance was still corrective in nature and not yet fully scheduled, and inventory data was not yet optimally utilized as a basis for managerial decision-making. The conclusion of this study emphasizes the need for strengthening facilities and infrastructure management to be more planned, preventive, and data-driven. Therefore, it is recommended that madrasahs develop a periodic maintenance system, optimize the digitization of facilities and infrastructure management, and improve human resource competencies to support the sustainability of learning quality. Keywords: facility and infrastructure management, learning quality, digitization of facility and infrastructure management Abstrak: Artikel ini mengkaji isu yang berangkat dari fakta sosial bahwa ketersediaan fasilitas pendidikan yang memadai belum selalu diikuti dengan pengelolaan yang optimal, khususnya pada aspek pemanfaatan, pemeliharaan, dan pengelolaan berbasis data. Dalam konteks pendidikan modern dan tuntutan peningkatan mutu pembelajaran, manajemen sarana dan prasarana menjadi faktor strategis karena berpengaruh langsung terhadap kenyamanan, efektivitas, dan kualitas proses belajar mengajar. Penelitian ini menggunakan pendekatan kualitatif dengan jenis studi kasus. Teknik pengumpulan data dilakukan melalui observasi, wawancara mendalam dengan kepala madrasah, wakil kepala bidang sarana dan prasarana, guru, serta peserta didik, dan dokumentasi. Analisis data dilakukan melalui tahapan reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa pengelolaan sarana dan prasarana di MAN 2 Kota Semarang telah berjalan cukup baik pada aspek perencanaan dan pengadaan, serta didukung oleh ketersediaan fasilitas yang relatif lengkap. Namun demikian, ditemukan bahwa pemanfaatan fasilitas belum merata, pemeliharaan masih cenderung bersifat korektif dan belum terjadwal secara menyeluruh, serta data